2003
DOI: 10.1029/2002jb002245
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent ocean bottom cable data in gas hydrate investigation offshore of Norway

Abstract: [1] A multicomponent seismic ocean bottom cable (OBC) line from the northern flank of the Storegga Slide offshore of Norway is the first OBC line ever acquired over a gas hydrate-related bottom simulating reflector (BSR). The seismic data are of very good quality, and display strong P-S converted wave reflections for the whole sediment column. All P-S reflections follow the sediment layers and are therefore interpreted to be caused by increased shear modulus and density due to sediment compaction. No P-S refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…The authors conclude that a geothermal gradient of 51.5 to 55.8°CÁkm -1 fits best the observed BSR at 250 to 300 mbsf in water depths ranging from 800 to 1250 m. Similar values around 55°C km -1 are reported by other authors as well (e.g. Mienert et al 1998;Andreassen et al 2003). However, there is a slight discrepancy between inferred geothermal gradients from the BSR depth, and the measurements stored in the HEAT database.…”
Section: The Age Of Crackssupporting
confidence: 61%
“…The authors conclude that a geothermal gradient of 51.5 to 55.8°CÁkm -1 fits best the observed BSR at 250 to 300 mbsf in water depths ranging from 800 to 1250 m. Similar values around 55°C km -1 are reported by other authors as well (e.g. Mienert et al 1998;Andreassen et al 2003). However, there is a slight discrepancy between inferred geothermal gradients from the BSR depth, and the measurements stored in the HEAT database.…”
Section: The Age Of Crackssupporting
confidence: 61%
“…The amplitude of some of the reflections from these layers changes markedly across the BSR, commonly with an associated change in polarity. Previous work on the data from the oceanbottom cable (Andreassen et al, 2003;Bünz and Mienert, 2004) and from individual OBS with shot lines along strike (Bünz et al, 2005) showed a downward reduction in Vp across the BSR of about 400 m/s, with no decrease in Vs. The results from HYDRATECH are in accord with these observations, but show that the reduction in Vp is laterally variable, dependent upon which layers are intersected by the BSR.…”
Section: Storeggamentioning
confidence: 99%
“…Methane hydrate has been sampled from pockmarks at the tops of similar chimneys lying 30-35 km to the east (Ivanov et al, 2007). At this site, a rectangular array of 21 OBS was deployed at the same position as a previous survey with an ocean-bottom cable (Andreassen et al, 2003;Bünz and Mienert, 2004), at the centre of which lies a geotechnical borehole that penetrates beneath the depth of the BSR (Bünz and Mienert, 2004). Samples of hydrate were not, however, successfully recovered from the borehole (Mienert and Bryn, 1997).…”
Section: Storeggamentioning
confidence: 99%
“…The BSR may indicate gas hydrate, or it may be a result of a diagenetic transformation of opal A to opal CT (Hammon and Gaither, 1983). Gas hydrate is commonly found in the sub-seafloor deposits in polar regions, where the pressure and temperature combine to render it stable (Andreassen et al, 2003). The BSR in such a case would occur at the base of the hydratebearing sediments, and the weaker reflections above the BSR would be due to cementation by the gas hydrate.…”
Section: The Bsrmentioning
confidence: 97%